KEPENTINGAN PEMERINTAH KABUPATEN GRESIK DALAM GOVERNMENT TO BUSINESS RELATIONS (G2B) DENGAN CARGILL - Diah Sulung Syafitri (UMY, 2016)
The study of international relations that has been changing from security issue to politic-economic issue creates few new actors, notably Multinational Corporations (MNC), and enhances transnational relations called Government To Business Relations (G2B). The existence of those multinational corporations foster the politic-economic policies aims to invite foreign investment which is needed by the developing countries, such as Indonesia. The lack of technology skill makes Indonesia’s natural resources only emerges in the head sector. It is general knowledge that the plantation sector of Indonesia experience that way. Indonesia is the third biggest producer of cocoa beans in the world, but its quality does not have good packaging to sell to international market since it is not being processed. Under decentralization policy, the government of Gresik Regency actively invites foreign investment to join development agendas in Gresik. It is proven that Cargill has chosen Gresik as the location of the building of the biggest cocoa-processing firm in Southeast Asia, eventhough Gresik is not the producer of cacao beans in Indonesia. This thesis will research about the interest of the government of Gresik Regency towards Government to Business Relations (G2B) with Cargill